The impact of ageing on savings: A panel data study among the OECD countries - Ferreira, Mariana Miguel dos Reis (2015)
Ageing has been pointed out as the most prominent demographic trend of the 21st century and is expected to impact economies at a micro and macro scale. One of the main consequences of this global phenomenon is the change in savings behaviour, which has been resulting in a decrease on the rate of savings. This thesis aims to study the impact of ageing on the gross savings rate through a panel data of 28 OECD countries observed between 1990 and 2013. The main ageing determinant considered in this study is the old age dependency ratio but some control variables as life expectancy, health expenditure and social expenditure with elderly, education level, unemployment and interest rate are also included. Non-stationarity and co-integration properties between gross savings and its drivers are studied and the long-run relationship is estimated using the Group Means Panel-Dynamic Ordinary Least Squares (PDOLS) framework. The findings suggest that ageing has a negative impact on savings, mainly through the negative influence of old age dependency ratio, health expenditure and social expenditure with elderly on the gross savings rate.